1971
DOI: 10.1128/jb.106.3.1034-1035.1971
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Trehalase from Pullularia pullulans

Abstract: Trehalase has been isolated from Pullularia pullulans. The enzyme, which is specific for trehalose, was purified approximately 800-fold. The optimal pH was found to be 4.0 and the Michaelis dissociation constant, Km. was determined to be 3.2 x 10-3 M. Trehalose has been found in microorganisms, vertebrates, invertebrates, and phanerogams (15). In fungi, trehalose functions as a reserve carbohydrate sustaining respiration and accelerating germination (6,7,14). Trehalose has recently been isolated from the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Another characteristic of the regulatory type of trehalase might be a higher Km than that for the nonregulatory trehalases. The Km values of the nonregulatory trehalases fall in the range of about 0.5 to 3 mM (70,74,81,82,108,109,128,134,139,208,211). Km values reported for regulatory trehalases are 4.5 (88), 10 (6), and 55 (198) mM.…”
Section: Nonregulatory and Regulatory Trehalasesmentioning
confidence: 94%
“…Another characteristic of the regulatory type of trehalase might be a higher Km than that for the nonregulatory trehalases. The Km values of the nonregulatory trehalases fall in the range of about 0.5 to 3 mM (70,74,81,82,108,109,128,134,139,208,211). Km values reported for regulatory trehalases are 4.5 (88), 10 (6), and 55 (198) mM.…”
Section: Nonregulatory and Regulatory Trehalasesmentioning
confidence: 94%
“…These data were taken as additional evidence for the existence of compartmentation between trehalose and trehalase. Other fungi in which trehalase was found only in the soluble fraction of cell extracts include Dictyostelium discoideum (82), Pullularia pullulans (109), and ascospores of Pichia pastoris (Thevelein, unpublished results). It was suggested that in spores of Dictyostelium discoideum, trehalose was localized in vesicles (62,114), as opposed to the localization of trehalase in the cytosol.…”
Section: Theveleinmentioning
confidence: 95%
“…Another characteristic of the regulatory type of trehalase might be a higher Km than that for the nonregulatory trehalases. The Km values of the nonregulatory trehalases fall in the range of about 0.5 to 3 mM (70,74,81,82,108,109,128,134,139,208,211). Km values reported for regulatory trehalases are 4.5 (88), 10 (6), and 55 (198) mM.…”
Section: Nonregulatory and Regulatory Trehalasesmentioning
confidence: 96%
“…Trehalases, trehalose-hydrolysing enzymes, have been isolated from many organisms (Hill & Sussmann, 1963; Killick, 1985; Merdinger et al, 1971; Retief & Hewitt, 1973; Arguelles & Gacto, 1985). Fungal trehalases are divided into acid trehalases and neutral trehalases (Thevelein, 1984).…”
Section: Introductionmentioning
confidence: 99%